Effects of antioxidants on pork production (Research, Society and Development, 2022)
The Brazilian pork industry has been recognized as one of the world's largest producers, currently holding the fourth position as the largest producer and exporter of pork. Pork is known for its presence of mainly polyunsaturated fatty acids (PUFAs), which makes it more susceptible to oxidation and rancidation, thus decreasing its shelf life. To minimize this oxidation, the practice of including antioxidant additives in the feed has been adopted, the main ones being ascorbic acid (vitamin C) and tocopherol (vitamin E). The main actions of antioxidants can be the interception and reduction of free oxygen, sequestering hydroxyl radicals, chelating metal ions, and decomposing compounds. The objective of this review is to approach the antioxidants in swine feeding and their effects on meat products from the industrialization process. The methodology employed in this review was a descriptive study, based on scientific articles published in different journals.